Word Sense Disambiguation using Clue Words - Dhungana, Udaya Raj; Shakya, Subarna (Journal of the Institute of Engineering, 2014)
This paper presents a new model to disambiguate the correct sense of polysemy word based on the related context words for each different sense of the polysemy word. The related context words for each sense are referred to as clue words for the sense. The WordNet organises nouns, verbs, adjectives and adverbs together into sets of synonyms called synsets each expressing a different concept. In contrast to the structure of WordNet, we developed a model that organizes the different senses of polysemy words based on the clue words. These clue words for each sense of a polysemy word are used to disambiguate the correct meaning of the polysemy word in the given context using any WSD algorithm. The clue word for a sense of a polysemy word may be a noun, verb, adjective or adverb. DOI: http://dx.doi.org/10.3126/jie.v10i1.10900 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 192–198